(untitled) (Swiss Medical Weekly, 2017)
OBJECTIVE Coronary artery bypass grafting (CABG) remains the gold standard for complex revascularisation in multivessel disease. The concept of the minimally invasive extracorporeal circulation circuit (MiECC) was introduced to minimise pathophysiological side effects of conventional extracorporeal circulation. This study presents early and long-term outcomes after CABG with use of MiECC in a single-centre consecutive patient cohort. METHODS From 1 January 2005 to 31 December 2010, 2130 patients underwent isolated CABG with MiECC at our centre. We evaluated morbidity and mortality follow-up data with a median follow-up of 3.6 years. Kaplan-Meier curves and estimates of the primary end-point for all-cause mortality were compared with the life expectancy of the general population. RESULTS Mortality in CABG patients was comparable to the general population beginning 1 year after surgery for the whole observation period. All-cause 30-day mortality was 0.8%. The mean estimated logistic EuroSCORE and EuroSCORE II were 5.8 ± 8.6 and 3.0 ± 5.1, respectively. Mean perfusion time was 71.1 ± 23.8 min with a cross-clamp time of 44.9 ± 16.3 min. Mortality was predicted by the presence of diabetes mellitus (odds ratio [OR] 1.85, 95% confidence interval [CI] 1.40–2.46; p <0.001), peripheral arterial disease (OR 2.36, 95% CI 1.64–3.38; p <0.001), severe obstructive pulmonary disease (OR 3.21, 1.42–7.24; p = 0.005), chronic renal failure (OR 3.68, 2.49–5.43; p <0.001) and transfusion of more than one unit of erythrocyte concentrate in the perioperative period (OR 1.46, 1.09–1.95; p = 0.015). Cerebrovascular events occurred in 36 patients (1.7%). CONCLUSION CABG with use of MiECC is associated with a mortality rate comparable to the overall life expectancy of the general population. MiECC is the first choice for routine and emergency CABG at our centre with a 30-day mortality rate of 0.8% and a low complication rate.